International Labor Flows and National Wages - Engerman, Stanley L.; Jones, Ronald W. (American Economic Review, 1997)
When income levels of some group in the economy fall behind those of others, the blame frequently is cast on the nature of international trading relationships. Such has been the case recently in the United States with the struggle to maintain real wages for relatively lessskilled workers. Much of the debate has asked how changes in world prices or in technology at home or abroad have altered wage rates (see e.g., Susan Collins, 1996; Jones and Engerman, 1996). In this note we focus on another potential culprit, immigration, and probe more widely into past historical experience in the United States and other countries when inflows of labor from abroad disturb wage rates for nationals. Such international labor flows could serve to enhance rather than to depress the earnings of the country's own laborers. If the question addressed concerns the effects of immigration on the welfare of the original inhabitants of a country, a disarmingly simple answer was provided some years ago by Harry Johnson (1967): as long as immigrants bring an accumulated bundle of labor and physical or human capital that is different from that possessed by local residents, the latter must gain from immigration. This is the basic gains-from-trade argument, appropriate only if the country originally did not engage in any other form of trade and if all residents held balanced portfolios of capital and labor. As well, it ignores the social costs incurred and extra taxes collected when migrants flow into a country. In this note we focus not on aggregate welfare effects, but on the effect of immigration on the return to some homogeneous national group of laborers. This question is the one that most sharply divides the views of labor economists from those of trade economists. On the one hand, increases in the supply of labor would seem naturally to depress the return to labor, but in the basic Heckscher-Ohlin trade model with two factors and two produced commodities, an inflow of labor can be absorbed with absolutely no change in wage rates as long as the terms of trade remain undisturbed. We begin by asking what some basic theoretical models tell us about this issue, before turning to the historical record. Simple theory reveals that there are two basic attributes of immigration that affect income distribution: relatively how substitutable immigrant labor is for the national labor force, and the occupations in which immigrants are allowed to work.